Sporadic Cloud-Based Mobile Augmentation on the Top of a Virtualization Layer: A Case Study of Collaborative Downloads in VANETs - Esteban Fernando Ordóñez-Morales; Martín López-Nores; Yolanda Blanco-Fernández; Efren Patricio Reinoso-Mendoza; Jack Fernando Bravo-Torres; José Víctor Saiáns-Vázquez; José Juan Pazos-Arias; Manuel Ramos-Cabrer; Alberto Gil-Solla (Journal of Advanced Transportation)
Current approaches to Cloud-based Mobile Augmentation (CMA) leverage (cloud-based) resources to meet the requirements of rich mobile applications, so that a terminal (the so-called application node or AppN) can borrow resources lent by a set of collaborator nodes (CNs). In the most sophisticated approaches proposed for vehicular scenarios, the collaborators are nearby vehicles that must remain together near the application node because the augmentation service is interrupted when they move apart. This leads to disruption in the execution of the applications and consequently impoverishes the mobile users’ experience. This paper describes a CMA approach that is able to restore the augmentation service transparently when AppNs and CNs separate. The functioning is illustrated by a NaaS model where the AppNs access web contents that are collaboratively downloaded by a set of CNs, exploiting both roadside units and opportunistic networking. The performance of the resulting approach has been evaluated via simulations, achieving promising results in terms of number of downloads, average download times, and network overhead.